Marking Fish with Fluorochrome Dyes. Issue 1 (2nd January 2020) - Lü, Hongjian; Fu, Mei; Zhang, Zhixin; Su, Shengqi; Yao, Weizhi
Abstract: Marking fish with fluorochrome dyes has the potential to produce detectable marks in otoliths, scales, fin rays, fin spines, and other bony structures based on differential staining of chemical dyes, and it is a widely used technique for mass-marking fish that included both teleosts and elasmobranchs. This technique, which has relatively economic advantages and simple marking process, can be applied to fish of all ages, and these fluorescent marks can be retained for several months and even years. Up to now, >200 fish species have been successfully marked by this marking technique. Fluorescent labeling is a practical and available marking technique for large-scale marking hatchery-reared fish. The methodology of fluorescent labeling is reviewed, including fluorochrome labeling dyes, application method, detection, and evaluation strategies. Aspects of practical applications, limitations, and supervision of fluorescent labeling are also discussed.